Reproductive factors and risk of total knee replacement due to severe knee osteoarthritis in women, the Singapore Chinese Health Study. Issue 8 (August 2019) - Leung, Y.-Y.; Talaei, M.; Ang, L.-W.; Yuan, J.-M.; Koh, W.-P.
Summary: Objectives: Knee osteoarthritis (OA) is more common in women, and may be related to reproductive or hormonal factors. We evaluated these factors with the risk of total knee replacement (TKR) for severe knee OA among women. Methods: The Singapore Chinese Health Study recruited 63, 257 Chinese aged 45–74 years from 1993 to 1998, and among them, 35, 298 were women. Information on height, weight, lifestyle factors, number of biological children, ages at menarche and menopause, and use of hormonal therapies was collected through interviews. Incident cases of TKR were identified via linkage with nationwide database. Results: There were 1, 645 women with TKR after mean follow-up of 14.8 years. Higher parity was associated with increased TKR risk in a stepwise manner ( P for trend <0.001). Compared to nulliparous women, those with ≥5 children had the highest risk [hazard ratio (HR) 2.01, 95% confidence intervals (CIs) 1.50–2.70]. The effect of parity on TKR risk was significantly stronger among lean women compared to heavier women; HRs (95% CIs) for highest parity was 4.86 (2.22–10.63) for women with body mass index (BMI) <23 kg/m 2 and 1.57 (1.14–2.14) for those ≥23 kg/m 2 ( P for interaction = 0.001). Earlier age at menarche and use of oral contraceptives were significantly associated with TKR in a stepwise manner ( P for trend ≤0.002). Age at menopause and use of hormonal therapy were not associated with TKR risk. Conclusion: Higher parity, earlier age of menarche and use of oral contraceptives were associated with increased risk of TKR for severe knee OA among women.